Phospholipase C From Alternaria alternata Is Induced by Physiochemical Cues on the Pear Fruit Surface That Dictate Infection Structure Differentiation and Pathogenicity - Huang, Yi; Li, Yongcai; Li, Dongmei; Bi, Yang; Prusky, Dov B.; Dong, Yupeng; Wang, Tiaolan; Zhang, Miao; Zhang, Xuemei; Liu, Yongxiang (Frontiers in Microbiology, 2020)
To investigate the mechanisms of phospholipase C (PLC)-mediated calcium (Ca2+) signaling in Alternaria alternata, the regulatory roles of PLC were elucidated using neomycin, a specific inhibitor of PLC activity. Three isotypes of phospholipase C designated AaPLC1, AaPLC2, and AaPLC3 were identified in A. alternata through genome sequencing. qRT-PCR analysis showed that fruit wax extracts significantly upregulated the expression of all three PLC genes in vitro. Pharmacological experiments showed that neomycin treatment led to a dose-dependent reduction in spore germination and appressorium formation in A. alternata. Appressorium formation was stimulated on hydrophobic and pear wax-coated surfaces, but was significantly inhibited by neomycin treatment. The appressorium formation rates of neomycin treated A. alternata on hydrophobic and wax-coated surfaces decreased by 86.6% and 47.4%, respectively. After 4 h of treatment, exogenous CaCl2 could partially reverse the effects of neomycin treatment. Neomycin also affected mycotoxin production in Alternariol (AOH), Alternariol monomethyl ether (AME), Altenuene (ALT) and Tentoxin (TEN), with exogenous Ca2+ partially reversing these effects. These results suggest that PLC is required for the growth, infection structure differentiation, and secondary metabolism of A. alternata in response to physiochemical signals on the pear fruit surface.